2012
DOI: 10.1245/s10434-012-2531-z
|View full text |Cite
|
Sign up to set email alerts
|

American College of Surgeons Oncology Group (ACOSOG) Z0011: Impact on Surgeon Practice Patterns

Abstract: Introduction The ACOSOG Z0011 trial has been described as practice-changing. The goal of this study was to determine the impact of the trial on surgeon practice patterns at our institution. Methods This is a review of practice patterns comparing the year before release of Z0011 to the year after an institutional multidisciplinary meeting discussing the results. Patients meeting Z0011 inclusion criteria were identified. Clinicopathologic data were compared between the cohorts. Results There were 658 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
104
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(111 citation statements)
references
References 19 publications
4
104
0
3
Order By: Relevance
“…3 The Z0011 trial has been proclaimed a practice changer, with most surgical practices rapidly accepting Z0011 criteria as part of standard axillary management allowing for the avoidance of ALND in patients with up to 2 lymph nodes with metastatic disease. [4][5][6] Despite criticisms concerning the study's lack of long-term follow up, low patient accrual, and reported protocol violations, Z0011 has made a significant impact on patients with primary BC by improving quality of life without compromising overall survival. 7 In 2014, the American Society of Clinical Oncology (ASCO) published updated guidelines regarding SLNB for patients with early-stage BC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The Z0011 trial has been proclaimed a practice changer, with most surgical practices rapidly accepting Z0011 criteria as part of standard axillary management allowing for the avoidance of ALND in patients with up to 2 lymph nodes with metastatic disease. [4][5][6] Despite criticisms concerning the study's lack of long-term follow up, low patient accrual, and reported protocol violations, Z0011 has made a significant impact on patients with primary BC by improving quality of life without compromising overall survival. 7 In 2014, the American Society of Clinical Oncology (ASCO) published updated guidelines regarding SLNB for patients with early-stage BC.…”
mentioning
confidence: 99%
“…9 Although the ASCO guidelines provide an online appendix addressing pathologic evaluation of SLNB and known limitations of frozen section diagnosis, the guidelines do not encourage or discourage the use of frozen section diagnosis for SLNB. 8 Although much has been published regarding changes in surgical practice since Z0011, 5,6,[10][11][12] to our knowledge this is the first study to acknowledge Z0011's effect on pathology practice. Prior to the published Z0011 trial results, the vast majority of SLNBs were sent for frozen section diagnosis at our institution.…”
mentioning
confidence: 99%
“…SLNB sonucu pozitif olan hastalarda, neoadjuvan tedavi sonrasında her durumda aksiller diseksiyon uygulanıyor. Neoadjuvan tedavi öncesi SLNB ile aksillası negatif hastalarda KT sonrasında aksiller girişim yapılmıyor (13). Neoadjuvan KT öncesinde İİAB ile aksiller metastaz saptanan ve seed yerleştirilen hastalara ise KT sonunda cerrahi sırasında, önce aksiler küçük bir kesi ile seed in bulunduğu nod çıkarılıyor, arkasından diseksiyon yapılıyor (10).…”
Section: Neoadjuvan Tedavi Yaklaşımlarıunclassified
“…Mastektomi yapılacak hastalarda SLN frozen değerlendirilmesi yapılıyor (touch imprint değil, frozen yapılı-yor). Mastektomi yapılacak hastanın RT alacağı kesinse yine frozen yapılmıyor (13,14). SLNB için lenfosintigrafi ve gama prob kullanılıyor.…”
Section: Sentinel Nod Yaklaşımlarıunclassified
“…2 However, the results of the INT09/98 are convincing and it is impossible not to view them in light of another outstanding "practice-changing trial," the American College of Surgeons Oncology Group Z0011 study, 3 with an impelling need to improve these results. 4 Therefore, the question is whether information regarding the axilla may really influence OS, DFS, and indications for adjuvant chemotherapy in patients with operable breast cancer. 5 A possible shortcoming of the INT09/98 trial is that the biological characteristics considered were lymph node status, estrogen receptor (ER) status, and tumor grade for patients in the group receiving quadrantectomy with AD and ER status, tumor grade, human epidermal growth factor receptor 2 status, and laminin receptor status in the group of patients treated with quadrantectomy without AD.…”
mentioning
confidence: 99%